Kapitalisasi Pengelolaan Pariwisata Berbasis Komunitas (Studi Kasus Wisata Sumber Maron, Desa Karangsuko, Kecamatan Pagelaran, Kabupaten Malang) - Zahrotun Nafi'ah; Danisa Thalita Laras Ayu; Raden Arvin Praja Kurniawan (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
In Malang Regency there are attractions that utilize water resources, these are Source of Maron. Source of Maron is one of the natural attractions which is precisely located in Adiluwih Hamlet, Karangsuko Village, Pagelaran District, Malang Regency. Sumber Maron tourism development can be said to be greatly improved , this can be seen from the increasing number of visitors every day. However, in its management Sumber Maron paid less attention to the impact of its development on the environment. So in this study, the author wants to examine the dynamics of capitalism in Sumber Maron. This research uses descriptive qualitative research that seeks to describe and interpret what is happening. Tourism management has both positive and negative impacts, namely damage to the environment around tourism due to capitalization that occurs in the tourism sector. The capitalization action taken is the conversion of the function of agricultural land into a permanent stall to meet the needs of tourists.